x 5 − 7 x 4 − 1 = 0
If r 1 , r 2 , r 3 , r 4 , r 5 are the roots of the equation above, find the value of expression below.
r 1 2 0 1 + r 2 2 0 1 + r 3 2 0 1 + r 4 2 0 1 + r 5 2 0 1
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Oh that's too easy liked it and upvoted!
Very nice.
But i solved it using a lot of calculations by using newton sum.
Nice problem!!
We can rewrite the equation as
x 4 = x − 7 1
x → r i where i = 1 , 2 , 3 , 4 , 5
r i − 7 = r i 4 1
raising the power to five
r i 2 0 1 = ( r i − 7 ) 5
the required expression is i = 1 ∑ 5 r i 2 0 1 = i = 1 ∑ 5 ( r i − 7 ) 5
Expanding the expression, we get
i = 1 ∑ 5 ( r i 5 − 7 ( 1 5 ) r i 4 + 7 2 ( 2 5 ) r i 3 − 7 3 ( 3 5 ) r i 2 + 7 4 ( 4 5 ) r i − 7 5 ( 5 5 ) )
now applying newtons identities, which states
P ( x ) = a k x k + a k − 1 x k − 1 + . . . . . a 1 x + a 0 e 1 = ∑ α i = − a k a k − 1 e 2 = ∑ α i α j = a k a k − 2 e k = ∏ α i = ( − 1 ) k a k a 0 P i = j = 1 ∑ k α j i F o r i ≤ k − 1 P k − 1 = e 1 P k − 2 − e 2 P k − 3 + . . . . + ( − 1 ) k − 2 e k − 1 ( k − 1 ) F o r i ≥ k P i = j = 1 ∑ k ( − 1 ) j + 1 e j P i − j
Now
( e 1 = 7 e 2 = 0 e 3 = 0 e 4 = 0 e 5 = 1 P 0 = 5 P 1 = 7 P 2 = 7 2 P 3 = 7 3 P 4 = 7 4 P 5 = 7 5 + 5
[ ∵ P 3 = e 1 P 1 − e 2 P 1 + e 3 × 3 P 5 = e 1 P 4 − e 2 P 3 + e 3 P 2 − e 4 P 1 + e 5 P 0 ]
We finally get after plugging in the values
= 7 5 + 5 − 5 × 7 5 + 1 0 × 7 5 − 1 0 × 7 5 + 5 × 7 5 − 5 × 7 5
= 7 5 + 5 − 5 × 7 5 = − 6 7 2 3 3
can the problem be solved without using newton's identities ?
Log in to reply
I don't know, but it seems to be a difficult rather tedious approach without using newtons identities
Log in to reply
Nice Solution, my approach was slightly different, so I did a lot of calculations. Try this
Problem Loading...
Note Loading...
Set Loading...
x 5 − 7 x 4 − 1 = 0 we get that ∑ ( x ) = 7 for roots r i 1 , the equation becomes y = x 1 y 5 1 − 7 y 4 1 − 1 = 0 y 5 + 7 y − 1 = 0 since s 1 = s 2 = s 3 = 0 , p 1 = p 2 = p 3 = 0 where s n is nth symmetric sum and p n is nth power sum. so y 5 = − 7 y + 1 − − ( 1 ) y 2 0 = 2 4 0 1 y 4 + i r r e l e v e n t + 1 irrelevent because sum of all y , y 2 , y 3 is 0: ∑ y 2 0 = 2 4 0 1 ∑ ( y 4 ) + 5 ( 1 ) − − y 4 = − 7 + y 1 = − 7 + x ∑ y 4 = − 3 5 + ∑ x = − 3 5 + 7 = − 2 8 ∑ y 2 0 = 2 4 0 1 ∗ − 2 8 + 5 = − 6 7 2 2 3